Ethnomethodology’s Program - Garfinkelis, Haroldas (Sociologija. Mintis ir veiksmas, 2011)
Translation: translated from English by Gracija Pleikienė. This text by Harold Garfinkel – Ethnomethodology’s Program – was published in Social Psychology Quarterly (1996, Vol. 59 No. 1, 5–21). American Sociological Association (ASA) gave permission to republish the text in VU and KU scientific journal Sociologija. Mintis ir veiksmas (Permission No. 005833, July 5, 2011).